Six Recommendations to Build Legitimacy for Translational Research Organizations - Rosser, Christian; Sager, Fritz; Leib, Stephen L. (Frontiers in Medicine, 2020)
Translational Research Organizations (TROs) face specific challenges to secure resilience and longevity. This focus article provides the rationale for six hands-on recommendations for the management of legitimacy building in TROs.